Endovascular treatment of extracranial carotid artery aneurysms using self-expandable covered stent grafts: A single center retrospective study. (February 2022) - Gao, Peixian; Qi, Jiaxin; Wang, Mo; Li, Gang; Yang, Le; Dong, Dianning; Wu, Xuejun
Objectives: This study was aimed to evaluate the safety and efficacy of endovascular treatment of extracranial carotid artery aneurysms (ECAAs) using self-expandable covered stent grafts. Methods: All patients with ECAA at a single institution were reviewed from February 2014 to February 2020. Eight consecutive patients (three men, mean age 64.5 years) treated with endovascular repair with self-expandable covered stent graft were retrospectively reviewed. Patient characteristics, angiographic results, and follow-up outcomes were retrospectively recorded. Access to ECAA was gained via a femoral approach or a direct puncture of common carotid artery after surgical exposure because of kinking of the aortic arch and common carotid artery. A self-expandable covered stent graft (Viabahn; W. L. Gore, Flagstaff, AZ) was deployed to exclude the aneurysm. Results: Based on imaging features, there were five peudoaneurysms and three true aneurysms. The technical success rate was 100%. Cerebral protection devices were not used in all the patients during the procedures. Immediate absolute obliteration of the ECAA with no endoleak was documented in all the patients. Perioperative complications included one internal carotid-cavernous sinus fistula, one bleeding at the puncture site, and one stroke. The mean follow-up period was 35.5 months (range, 9–72 months). All the patients were alive, with an obligation rate of 100%. No transient ischemia attack, stroke, or reoccurrence of symptoms was identified during the follow-up period. Radiological examinations identified patency of the stent grafts and revealed no endoleaks, stent fracture, stent migration, or aneurysm rupture. Conclusions: Endovascular treatment of ECAAs with self-expandable covered stent grafts appears to be a safe and feasible alternative for traditional open surgery, especially in the challenging anatomy and instable physical conditions. Although cerebrovascular accidents can occur as the result of hemodynamic changes during the perioperative period, the minimal alternative can yield satisfactory midterm follow-up clinical outcomes.